The 5th International Conference on Semiotics of Culture & Visual Communication (GOLDEN BEE 16) - Mouzouropoulos, Theseas (My University, 2024)
GLOBAL POSTER LANGUAGE ANY TYPES AND GENRES OF POSTERS WITHOUT THEMATIC FRAMES AND RESTRICTIONS / THE MAIN PROJECT OF THE BIENNALE Golden Bee 16 Global Biennale of Graphic Design received more than 20,000 entries from 55 countries. The 16 members of the Pre-Selection Committee selected the works in 16 competitive categories to participate in several exhibitions in Moscow and many other Russian cities from Kaliningrad to Vladivostok
Keywords: poster design; graphic design